Physical and mental health of behavioural health certified peer specialists in four US states - Judith A Cook; Jane K Burke-Miller; Morgan Pelot; Jessica A Jonikas; Laysha Ostrow (BMJ Mental Health)
Background Little is known about the health and healthcare needs of the behavioural health peer specialist workforce in the USA. This study explored the physical and mental health-related quality of life (QOL) of a US multistate cohort of certified peer specialists, and factors associated with health-related work absences among those employed in peer specialist positions.Methods Data come from 419 participants surveyed 18 months after state certification as part of a 2-year longitudinal cohort study of peer specialists in four US states. Measures included the Veterans RAND 12 Item Health Survey, the Epidemic-Pandemic Impacts Inventory and items from the National Health & Nutrition Examination Survey and Medical Expenditure Panel Survey. Multivariable hierarchical regression models predicted physical and mental health-related QOL and occurrence of work absences due to health.Results High rates (60%) of multiple physical health conditions characterise both those working in peer support positions and those not employed. Better physical health-related QOL was associated with younger age, not having multiple physical health conditions, not experiencing cost as a barrier to healthcare and not being enrolled in Medicaid or Medicare. Better mental health-related QOL was associated with older age, being Black/African-American, employment in peer support positions, moderate exercise, having a usual source of medical care and cost not being a barrier to care. Among those employed as peer specialists, health-related work absences were associated with physical and mental health QOL and other factors.Conclusions Certified peer specialists have high rates of physical comorbidities, and this affects their mental and physical health-related QOL and likelihood of working in peer support positions. Factors such as cost, having a regular source of healthcare, insurance coverage and demographic features are also associated with their QOL. These findings can inform efforts to attract and retain certified peer specialists in the behavioural health workforce.